Perinatal mortality - Ticona Rendón, Manuel (2015)
The perinatal mortality indicates the level of development and quality of health of the people and to measure the health of the conceptus during the last two months of fetal life and the first 6 days after birth. Peru has marked structural contrasts in Latin America and the Caribbean. The greatest differences are in the maternal mortality ratio (2.3 times) and less is 5 years (2 times), the perinatal mortality rate similar to the Latin American average. In the last fifteen years the proportion of neonatal mortality has increased, reaching 55% of infant mortality. In the first month of life, infants die mainly from suffocation, respiratory distress, infection or congenital malformation. L00% of neonatal deaths in 2002, 41% was the result of complications during delivery and immediate newborn care: 33%, complications related to pregnancy: 16%, complications in the first week of life and 10% result of complications after 7 days of life. Perinatal mortality is reviewed in Peru in the regional context and makes recommendations to decrease: the methodology used as perinatal risk, to involve all community organizations in perinatal care, fizar region Health Services in accordance with the Law of Coordinated and Decentralized National System of Health, provide appropriate care of obstetric and neonatal emergencies and use the epidemiological model proposed in the study "Risk Factors of Perinatal Mortality in Peru".